Genomic interplay in bacterial communities: implications for growth promoting practices in animal husbandry - Roy Chowdhury, Piklu; McKinnon, Jessica; Wyrsch, Ethan; Hammond, Jeffrey M.; Charles, Ian G.; Djordjevic, Steven P. (Frontiers in Microbiology, 2014)
The discovery of antibiotics heralded the start of a ‘Golden Age’ in the history of medicine. Over the years, the use of antibiotics extended beyond medical practice into animal husbandry, aquaculture and agriculture. While the ‘Golden Age’ featured the rapid discovery of a series of new classes of antibiotics, the current discovery/development pipeline has been less productive. We are now faced with the threat of diseases mediated by pathogenic bacteria that are resistant to all major classes of antibiotic. Evolution of bacteria resistant to multiple antibiotics results from the inherent genetic capability that bacteria have to adapt rapidly to changing environmental conditions. Consequently, under antibiotic selection pressures, bacteria have acquired resistance to all classes of antibiotics, sometimes very shortly after their introduction. Multiple drug resistant (MDR) bacteria are found worldwide and are possibly signalling the end of the antibiotic era. Arguably, the evolution and rapid dissemination of MDR genes en-masse across microbial pathogens is one of the most serious threats to human health. In this context, effective surveillance strategies to track the development of resistance to multiple antibiotics are vital to managing global infection control. These surveillance strategies are necessary for not only human health but also for animal health and plant production. Shortfalls in the present surveillance strategies need to be identified. Raising awareness of the genetic events that promote co-selection of resistance to multiple antimicrobials is an important prerequisite to the design and implementation of molecular surveillance strategies. In this review we will discuss how surveillance strategies are important for our understanding of the possible relationship between the use of low-dose antibiotics in animal husbandry and evolution of MDR in Gram-negative bacteria.